Constraining the Decline of the Lunar Dynamo Field at ≈3.1 Ga Through Paleomagnetic Analyses of Apollo 12 Mare Basalts. Issue 3 (9th March 2021) - Strauss, B. E.; Tikoo, S. M.; Gross, J.; Setera, J. B.; Turrin, B.
Abstract: Recent paleomagnetic studies of lunar rocks have suggested that the magnetic field of the Moon reached peak intensities on the order of ≈77 μT between 3.85 billion and 3.56 billion years ago (Ga) and subsequently declined to surface intensities of ≈4 μT by 3.19 Ga. However, this decline in the intensity of the lunar field has only been shown in a small number of samples, presenting challenges for constraint of its timing and thus the dynamo generation mechanisms that could be responsible. We present microscopic and magnetic analyses of Apollo samples 12008, 12009, and 12015, three fine‐grained mare vitrophyre basalts with high magnetic fidelity, indicating that these samples were not magnetized in conditions consistent with a planetary magnetic field exceeding 4–7 μT during their formation. We further report updated radiometric ages for samples 12008 and 12009 and the first‐ever radiometric age for sample 12015, dating this lunar field intensity constraint to ≈3.1 Ga. These data are consistent with results of previous work on the initial decline of the Moon's magnetic field and confirm that the mechanism of lunar dynamo generation changed dramatically between 3.6 and 3.1 Ga. Plain Language Summary: Although the Moon does not have a magnetic field in the present day, records of an ancient lunar field have been found in rock samples collected during the Apollo missions. Between 3.85 billion and 3.56 billion years ago, the Moon's magnetic field was as strong as the Earth's field is today, but samples from 3.19 billion years ago have shown records of a much weaker field. To understand what caused this change in the strength of the field, we need evidence from more samples capable of recording weak magnetic fields around when the field declined. In this study, we analyzed three volcanic rock samples from the Moon and showed that all three are able to record weak magnetic fields, but none of them recorded such fields when they formed. We also determined the ages of these rocks and found that they are all about 3.1 billion years old. This means that 3.1 billion years ago, the Moon had an extremely weak magnetic field. This conclusion agrees with previous studies and confirms that the strength of the field changed very quickly, which must have been the result of a rapid and major change in how the field was produced. Key Points: No evidence for lunar fields >7 μT at ≈3.1 Ga Initial lunar dynamo decline spanning ≈370 Ma indicates two stability regimes Grain size may control magnetic fidelity in lunar rocks